Ethnomathematics Meets Computational Thinking: Developing a Learning Model for Mathematical Problem-Solving - Eka sastra Sastrawati; Andi Gusmaulia Eka Putri; Ahmad Faisal Hidayat; Yantoro Yantoro; Violita Zahyuni (AL-ISHLAH: Jurnal Pendidikan, 2026)
Mathematical problem-solving and computational thinking (CT) are essential competencies in 21st-century mathematics education. This study developed and evaluated an ethnomathematics-based learning model integrated with CT to enhance elementary students’ problem-solving skills. Using a Research and Development approach guided by the ADDIE framework, the model incorporated local Jambi cultural artifacts, including traditional batik geometric patterns, architectural designs, and community-based measurement practices. The model was implemented over eight instructional sessions (four weeks) with 30 fifth-grade students. Expert validation was conducted by three specialists using a five-point Likert scale assessing content, instructional design, and language clarity, yielding a high validity index (M = 4.06/5.00; 81.2%). Effectiveness was examined using a one-group pretest–posttest design (without a control group). Mathematical problem-solving was measured through an essay-based test aligned with Polya’s stages, while CT was assessed using a rubric-scored written test covering decomposition, pattern recognition, abstraction, and algorithmic thinking (Cronbach’s α 0.80). Results showed significant improvements in mathematical problem-solving (pre: M = 68.00, SD = 7.85; post: M = 86.00, SD = 6.92; p .001) and CT (pre: M = 65.15, SD = 8.10; post: M = 83.30, SD = 7.25; p .001), with a large effect size (d = 2.45). These findings provide preliminary evidence for integrating ethnomathematics and CT, warranting larger controlled studies to confirm generalizability.